Understanding Nonverbal Communication Across Cultures Perception of International Students in University Utara Malaysia - Attoumi, Mohamed Aabeid Khalfalla (2010)
A study of 170 postgraduates international students in College of Arts and Sciences (CAS) at University Utara Malaysia showed a positive relationship between perception of non verbal communication with misunderstanding and conflict and there was negative relationship between perception of non verbal communication and frequency interaction. This finding revealed the ability of international students in interpreting the usage of nonverbal communication of the host society. The main purpose of this study was to examine the percepception of non verbal communication can lead to misunderstanding, conflict and frequncy of students interaction. In the other hand this study also was to examine whether there are differences in perception of non verbal communication from demographic factors such as gender, nationality and travelling. quantitative methodology, using principles of symbolic interaction theory was used for the study. Information was gathered by survey questionnaire and a modified questionnaire from Richmond, McCroskey, and Johnson (2003). Result from this study supported that perception of non verbal communication among postgraduate international students in University Utara Malaysia can lead to misunderstanding, conflict and frequency intraction, whereas the higher differences preception of non verbal communication from demographic factor is Arab nationality.